Pemberian sari ikan kutuk (Channa striata) pada penyakit ginjal kronik dengan edema anasarka, diabetes melitus, dan hipertensi: Case report - Khanifa, Khoirunisa; Larasati, Meirina Dwi; Yuniarti; Setyaningrum, Luhur Ngudi (Jurnal Kesehatan Andalas, 2026)
Administration of snakehead fish (Channa striata) extract in chronic kidney disease with anasarca edema, diabetes mellitus, and hypertension: A case report Chronic kidney disease (CKD) is a global health problem often accompanied by complications such as anasarca edema, anemia, and protein-energy malnutrition, particularly in patients with diabetes mellitus and hypertension. This condition requires innovative nutritional strategies to support clinical recovery. Snakehead fish (Channa striata), which is rich in protein, essential amino acids, and micronutrients, has been suggested as a potential supportive therapy. Scientific evidence regarding its benefits in CKD management remains limited. This case report presents nutritional care for a male patient with stage V CKD, anasarca edema, diabetes mellitus, and hypertension. The identified nutritional problems included decreased renal function requiring hemodialysis and endocrine metabolic disturbances; therefore, the nutritional intervention focused on a high-protein, low-simple-carbohydrate diet, Oral Nutrition Support (ONS), and snakehead extract supplementation (50 mL/day for six days). Monitoring outcomes showed an increase in dietary intake up to 75% of requirements, improvement in hemoglobin levels from 8.2 g/dL to 8.5 g/dL, and clinical improvements, including reduced nausea, decreased edema, and lowered blood pressure from 203/106 mmHg to 146/72 mmHg. Snakehead extract supplementation has the potential to serve as an effective supportive intervention to improve hemoglobin levels, clinical status, and nutritional outcomes in CKD patients with complications. Keywords: anasarca edema, chronic kidney disease, diabetes mellitus, nutritional intervention, snakehead fish